HISTOPATHOLOGICAL FINDINGS OF THE LUNGS IN A BOER GOAT WITH CASEOUS PNEUMONIA: A CASE REPORT - Pahendra, Muhammad Arung Maugi; Adhisty, Andreana; Iqbal, Ghina Rizqi; Amalia, Annisa Fadilah; Meirizka, Annisa Zahra; Iliyina, Fatimah Nur; Mokobombang, Nur Herlinda; Arman, Frisca Muthia; Agustina, Wulan Tri; Rusmin, Muhammad Muslim Abdillah (Buletin Veteriner Udayana, 2026)
Pneumonia is a multifactorial disease in which various etiological agents play important roles in its pathology and pathogenesis. Identification of circulating pathogens in a specific area is essential for accurate diagnosis and effective disease control strategies. Bacterial culture remains the gold standard for confirming bacterial infections and can be complemented by histopathological examination to characterize pulmonary lesions. This case report aimed to describe the gross and histopathological changes observed in a Boer goat diagnosed with pneumonia. An approximately 6-year-old male Boer goat was found dead in the goat housing facility at the Faculty of Animal Science, Hasanuddin University. A complete necropsy was performed immediately on site, and lung tissue samples were collected for histopathological examination at the Laboratory of Pathology, Veterinary Medicine Study Program, Faculty of Medicine, Hasanuddin University. Tissue sections were processed and stained with Hematoxylin and Eosin (H&E) and subsequently examined microscopically. Histopathological examination revealed hyaline membrane formation along the alveolar epithelium, pulmonary hemorrhage, and emphysema characterized by alveolar rupture and coalescence. The main lesions consisted of tubular granuloma formation and caseous necrosis, findings consistent with caseous pneumonia. These findings provide important pathological evidence supporting the diagnosis and contribute to a better understanding of pulmonary lesions in Boer goats.